Epidemiologic Study of Periodontal Conditions in Patients Undergoing Renal Dialysis - Kataoka, Masatoshi; Shinohara, Hiroyuki; Ohba, Takanobu; Akazawa, Kayoko; Ninomiya, Yohsuke; Kido, Jun-ichi; Nagata, Toshihiko; Tono, Sayuri; Kirino, Akinori; Akimaru, Noriko; Ishimoto, Tomoko; Nakamura, Teruo (Nihon Shishubyo Gakkai Kaishi (Journal of the Japanese Society of Periodontology), 2000)
Some 180, 000 patients are currently undergoing renal dialysis in Japan. Dialysis does not, however, compensate for all kidney functions, e. g., erythropoietin production and vitamin D3 activation, which are very important reactions in the human body, are both inhibited. Osteoporotic disorder resulting from these functional deficiencies is a prominent side effect in renal dialysis patients. We suspect chronic renal failure to be a risk factor in periodontal disease. To determine the relationship between periodontitis and renal failure, we studied periodontal conditions in 38 subjects undergoing renal dialysis, together with a control group of 42 similar-aged healthy subjects. Community periodontal index of treatment needs (CPITN) assessment showed that dialysis patients, at 2.4±0.1, scored higher than controls, at 1.9±0.1 (p<0.05). No difference was seen between groups in the simplified calculus index (CI-S) score. The number of missing teeth, at 6.1±1.3, was 2.2 times greater in dialysis patients than in controls, at 2.8±0.8 (p<0.05). When patients were divided into 4 groups by dialysis duration, no significant difference was observed in any index. No correlation was seen between blood concentration of parathyroid hormone (PTH) and alveolar bone height or between PTH and CPITN. Of the 38 dialysis patients, 7 suffered fromdiabetic nephropathy, and most suffered from severe periodontitis. Compared to the other 31 patients, those having diabetic nephropathy showed an increase in missing teeth, from 3.9±1.1 to 15.9±3.6 (p<0.05), and a decrease in alveolar bone height from 79±1% to 58±6% (p<0.05). When the 31 nondiabetic dialysis patients were compared to controls, these patients, at 2.3±0.1, scored a higher CPITN than controls, at 1.9±0.1 (p< 0.05), indicating that nondiabetic patients suffered more from periodontitis than healthy subjects. This suggests that patients with chronic renal failure undergoing dialysis are at risk for periodontitis and that those with diabetic nephropathy suffer more from severe periodontitis. J.Jpn. Soc. Periodontol., 42: 307-313, 2000.